LOVE AS THE FOUNDATION FOR THE FORMATION OF RELIGIOUS CHARACTER IN ISLAMIC EDUCATION - Roshy Nur Khoiroh; Ahmad Barizi; Nabilatun Mubasyiroh (Religi: Jurnal Studi Agama-agama, 2026)
Islamic religious education faces a fundamental problem: the dominance of cognitive approaches that neglect the affective dimension results in shallow value internalization, leaving students' religious character fragile against the pervasive negative influences of the digital age. This study employs a qualitative library research approach through thematic analysis, cross-source interpretation, and source triangulation. The theoretical framework rests on the concept of mahabbah as articulated by Al-Ghazali, who positions love as the pinnacle of spiritual development and the engine of intrinsic motivation; Rabi'ah Al-Adawiyah, who emphasizes the purity of divine love as a prerequisite for authentic value internalization; and Ibn Miskawayh, who grounds love as the ethical foundation of social relations and moral excellence integrated with the Love-Based Curriculum of Indonesia's Ministry of Religious Affairs. The findings demonstrate that mahabbah functions as a transformative force unifying the spiritual, emotional, and social dimensions of character formation, producing graduates who are morally resilient, empathic, and oriented toward the common good.   Keyword: Love (Mahabbah); Love-Based Curriculum; Religious Character; Islamic Education. Digital Era   Pendidikan agama Islam menghadapi problem mendasar: dominasi pendekatan kognitif yang mengabaikan dimensi afektif menyebabkan nilai-nilai agama tidak terinternalisasi secara mendalam, sehingga karakter religius peserta didik rapuh di tengah derasnya pengaruh negatif era digital. Kajian ini menggunakan pendekatan kualitatif berbasis studi kepustakaan (library research) dengan analisis tematik, interpretasi lintas sumber, dan triangulasi data. Kerangka teori bertumpu pada konsep mahabbah menurut Al-Ghazali yang menempatkan cinta sebagai puncak spiritual dan motor motivasi intrinsik, Rabi'ah Al-Adawiyah yang menekankan kemurnian cinta sebagai syarat internalisasi nilai, dan Ibnu Miskawaih yang menjadikan cinta sebagai fondasi relasi sosial dan kesempurnaan akhlak, diintegrasikan dengan Kurikulum Berbasis Cinta Kementerian Agama RI. Hasil kajian menunjukkan bahwa mahabbah berperan sebagai kekuatan transformatif yang menyatukan dimensi spiritual, emosional, dan sosial dalam pembentukan karakter religius yang holistik, tangguh secara moral, dan berorientasi pada kemaslahatan bersama.   Kata kunci: Cinta(Mahabbah); Kurikulum Berbasis Cinta; Karakter Religius; Pendidikan Islam. Era Digital